The use of clinical role-play and reflection in learning therapeutic communication skills in mental health education: an integrative review - Ronning, Solrun Brenk; Bjorkly, Stal (Advances in medical education and practice, 2019)
An important goal in mental health education is for students to develop their ability to provide care and help to people with different degrees of mental problems. Positive experiences with the use of clinical role-play and subsequent reflection inspired us to investigate whether previous empirical studies had evaluated similar methods of teaching and to scrutinize the effects on students' development of therapeutic skills and clinical reflection. An integrative review was conducted to search the literature for findings from both qualitative and quantitative research. Systematic searches of literature were done in Ovid (MEDLINE, PsycInfo), Cinahl, Cochrane, ScienceDirect, SweMed, Norart, ProQuest, and Google Scholar. The systematic literature search provided 42 full-text articles and four articles met the inclusion criteria. The results suggest that role-play in health education enhances students' therapeutic and communicative skills. Nevertheless, there is limited research on the use of role-play in teaching therapeutic skills, and few studies that investigate how role-play affects students' reflections on own practice. The literature search did not discover studies investigating whether practicing role-play in educational settings has consequences for clinical practice. Based on this current review, role-playing in supervised groups seems to promote reflection and insight not only for students in the patient and therapist roles, but also for peers observing the group sessions. According to the included studies, clinical role-play facilitates helper-user equality and increases students' involvement, self-efficacy, and empathic abilities in mental health practice.